Interpretation of Birrul Walidayn in Surah Al-Isra [17]: 24 (A Comparative Study of Tafsir Al-Azhar and Marah Labid) - Alimuddin, Muhammad Faqih; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Devotion to both parents is a commendable trait often referred to as "birrul walidayn" in Arabic. A child's devotion to their parents may not always be proportional to the sacrifices parents make for their children. Devotion to parents can be demonstrated through good service, polite words, and dedication to both of them. In this era, we often witness the phenomenon of children being disobedient to their parents, which certainly goes against what Allah SWT and Prophet Muhammad have commanded. The purpose of this research is to determine the interpretation of "birrul walidayn" in Surah Al-Isra [17]: 24 according to Tafsir Al Azhar and Marah Labid, as well as to compare the similarities and differences between the interpretations of "birrul walidayn" by these two interpreters. This study is based on existing literature. The Tafsir Al Azhar book by Hamka and the Tafsir Marah Labid book by Sheikh Muhammad Nawawi are the primary and secondary data sources that were used to support this topic. Journals, theses, scientific papers, and books were the secondary data sources. The method used in analyzing this writing is the muqaran method. Based on the data analysis conducted, from the interpretation of Surah Al-Isra verse 24, Buya Hamka and Sheikh Muhammad Nawawi agree that a child should take care of both parents with patience and sincerity, be humble towards them, and pray for them.